Developing a Realistic Learning Approach on Mobile-based Apps: An Ethnomathematics Tedhak Siten - Nuryadi, Nuryadi; Marhaeni, Nafida Hetty; Soviyati, Anik (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
Realistic mathematics learning by utilizing culture as well as integrating technology can be used as an ideal starting point for learning. This study was intended to develop a mobile learning-based mathematics device with a realistic learning approach in the context of the Tedhak Siten ceremony to improve students' critical thinking skills. This type of research was development research that refers to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study used the mobile learning application, the pretest, and post-test questions, in accordance with the expert validation questionnaire, the media expert validation questionnaire (3 experts), and the student response questionnaire from 32 students. The results revealed that the validity aspect obtained a good category from the media and material expert validator. It obtained a good category from the media expert validators and material experts. It turned out that the media expert's score was 58 and the material expert's 192. Both scores were in a Good category, thus the application was declared valid to be used. Furthermore, the practical aspect of students as users obtained a total score of 2055 and was included in the good category. The effectiveness aspect obtained a significant increase in pretest to posttest scores. It was obtained that the increase in the results of the pretest to the results of the posttest was 24.46. Since there is an increase in testing, it can be concluded that the mobile learning developed is effectively used for learning mathematics. Based on the results, mobile learning has met all the product quality criteria, namely valid, practical, and effective. Therefore, mobile learning with a realistic approach to mathematics using the Tedhak Siten ceremony can improve students' critical thinking skills and can be used for learning.